The Neurosurgery I Lived - Basso, Armando (Revista Argentina de Neurocirugía, 2024)
The history of Argentinian, Latin American and world neurosurgery is narrated in this first person essay by an undisputed reference in the specialty of the last 60 years, describing the evolution of the patients outcome leading by technological, scientific and therapeutic advances. From “macrosurgery” to microsurgery, Professor Dr. Basso describe a path of dedication, discipline and passion for art, which is both inspiring and stimulating.
Keywords: Armando Basso; History of the Neurosurgery; Microsurgery; Neuroanatomy